The last adventure of Constance Verity - Martinez, A. Lee (Martinez, A. Lee. Last adventure of Constance Verity, 2016)
"Granted a wish at birth, Constance Verity has become one of the world's great adventurers. A master of exotic martial arts and a keen detective, she is in possession of a collection of strange artifacts, which are mostly kept in unlabeled boxes in her apartment. Constance has spent the past twenty years saving the world, and she's sick of it. She wants an office job and a boyfriend who isn't going to get killed by who knows what, and she's figured out the way to get them: she's going to kill her fairy godmother--Grandmother Willow--who granted the wish--and reset her life. The problem is, saving the world is Constance's destiny. She's really good at it, and there are forces at work to make sure she stays in the job. Then again, it's also her destiny to have a glorious death."--